Design of visualization plots of industrial alarm and event data for enhanced alarm management. (October 2018) - Hu, Wenkai; Al-Dabbagh, Ahmad W.; Chen, Tongwen; Shah, Sirish L.
Abstract: The availability of large volumes of alarm & event data in complex industrial facilities has prompted the development of alarm management techniques and also resulted in a great demand to transform such data and derived results into effective visual forms. Even though good visualization applications can be found in many existing studies, systematic studies to the design of visualization plots are still rare in the area of industrial alarm monitoring. More efforts need to be devoted to enriching the family of visualization techniques, so as to help industrial practitioners in better understanding the behavior of alarm systems and to facilitate decision making for the enhancement of alarm management. This paper presents timely work in the design of visualization plots of alarm & event data. First, a comprehensive literature survey is carried out to investigate existing visualization techniques, which are categorized into three classes based on the input information. Problems in the existing studies are summarized and design requirements for visual analytics are presented. Then, design studies on the development of visualization plots are presented in three categories, including visualization towards overall performance, visualization towards pattern insights, and visualization towards realtime applications. Examples are provided to demonstrate the effectiveness and utility of these visualization techniques.